Perbandingan Efektivitas Pemberian Rebusan Jahe Dan Daun Mint Terhadap Mual Muntah Pada Ibu Hamil - Chatur Dhian Parwitasari; Sri - Utami; Siti Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This research aims to know the comparative effectiveness of the granting of the decoction of ginger and mint leaves to nausea to vomiting in pregnant women. Methods the study was quasi experimental with pretest-posttest design approach with two eksperiment. This research was conducted in the region work Puskesmas Garuda Soweto against 30 persons 1 trimester of pregnant women with pregnancy primipara, that is 15 expectant mothers group of ginger and 15 others group of mint leaves. Sampling method with a snowball by using the observation sheet gauge. Data analyzed with Mann Withney tests Test results obtained after giving ginger stew p-value (0.001) < α (0.05) so that it can be concluded there is a significant difference after awarding Ginger stew while the mint leaves obtained p-value (0.028) > α (0.05) Thus it can be concluded there is a significant difference after giving ginger stew while the mint leaves obtained p-value (0.028) > α (0.05) so that it can be concluded there is no difference after the granting of the decoction of leaves of mint. The results mean the rank obtained in the Ginger Group of 9,87 and 6,66 group mint leaves, ginger stew is summed up so that it can more effectively than with mint leaves. The results of this research to recommend the granting of boiled ginger and mint leaves to become one of the nursing interventions in addressing nausea vomiting in pregnant women with pregnancy 1st trimester primipara. Keywords : Ginger, Boiled mint leave, Nause and vomiting